TEACHING ENGLISH AS A FOREIGN LANGUAGE THROUGH ACTION TECHNIQUES - Anner, Catherine M. (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract We read, study, write, go to conferences and all in all develop our knowledge, but when we find ourselves in certain situations, new situations, our know-how will only be part of what we need. Our skills will be the instrument that our senses will guide to proper use. Experience forms us and with a certain touch of inspiration we can advance in our field with an attitude that will bring us into the reciprocal cycle of teaching. Let us have a closer look at how inspiration helped an English-as-a-second-language teacher develop her own personal style. We will see how English can be taught in English to young learners through actions and activities such as songs, stories, routines, gestures, funny voices and lots of surprises.